The Effects of Self-Monitoring on On-Task Behaviour of Students with Special Educational Needs in General Education Settings. - Sayar, Kübra; Güner, Nevin (International Journal of Disability, Development & Education, 2026)
On-task behaviour is the most basic behaviour needed in the lessons. Research indicates that on-task behaviour of students with special educational needs is lower than their peers. In this study, a multiple probe design was used to determine the effects of self-monitoring taught in a resource room on the students' self-monitoring usage and on-task level. It was also examined whether the effects of teaching were transferred to the general education class. Three 7–8 years old students with special educational needs participated in this study. The students utilised audio recording and earphones to monitor their on-task behaviour. The accuracy of student's monitoring was also assessed. The results showed that all participants acquired the ability to use self-monitoring, leading to improvements in their on-task behaviour. Additionally, the students were able to generalise the acquired skills, and two students were able to maintain their acquired skills. Comparing the students' on-task level before and after the intervention in the general education classroom without using self-monitoring revealed an increase in the students' on-task level ranging from 45% to 52%. Social validity findings of the study showed that students and teachers gave positive opinions regarding the study.